Investigation of Some Qualitative Characteristics of Sludge Produced in Hamadan Wastewater Treatment Plant and Its Application in Agricultural Lands - Reza Shokoohi; Samira Moradi; Zhila Ghavami; Azam Nadali; Raheleh Amiri (Hamadan University of Medical Sciences, 2019)
In this study, qualitative characteristics of the sludge produced in Hamadan wastewater treatment plant and the feasibility of its application in agricultural lands were investigated. Samples were taken from the primary and secondary sludge and indices such as VS/TS, PH, TKN, COD, TKN, SOUR, Na, Ca, SAR, heavy metals and biological properties (the mean fecal coliform count and the number of parasitic eggs) were measured. The results were compared with the United States Environmental Protection Agency (US EPA) standards (40 FCR-503). The results showed that the VS/TS ratio of the raw sludge was 0.8, 0.55, and 0.55 and that of the secondary sludge was 0.65, 0.28, and 0.32 for fall, winter, and summer, respectively. The average concentration of COD, TKN, SOUR, Na, and Ca for the initial sludge was 51283, 107, 0.50, 609, and 952 and for secondary sludge, it was 35595, 81, 4.90, 306, and 493 mg/L, respectively. The MPN for primary and secondary sludge was determined to be 19.83 × 106 and 186 × 106 , respectively and the average number of parasite eggs in primary and secondary sludge was 7.05 and 7.2 in 4 g of dry solids. Entamoeba coli had the highest number of parasite. The results of this study showed that the highest concentration of heavy metals in the sludge was 21396 mg/kg. The values obtained for the above-mentioned indices and heavy metals were in standards range. The results of this study show that none of the primary and secondary sludge samples has been properly stabilized. The values obtained for biological characteristics of sludge were not in the standard range. Therefore, it was revealed that the use of sludge for agriculture needed more stabilization.